The association of structural configurations of romantic relationships with beliefs about couple relationships: A social representations study - Luiz de Andrade, Alexsandro; Wachelke, Joao (Anales de Psicología / Annals of Psychology, 2011)
The study aimed at evaluating the role of structural configurations of romantic relationships on the social representations about couple relationships. Two dimensions were taken into account: relationship type and relationship duration, in four different block combinations: absence of relationship, informal relationship, short steady and long steady relationship. There were 160 Brazilian participants randomly selected from an internet sample in order to be balanced by relationship characteristics and sex. Participants completed a questionnaire that contained demographic items, items about their relationship characteristics and an association task with 'couple relationship' as the inducting expression. Prototypical analysis, a technique based on frequency counts and evocation ranks, was employed to analyze data. Results show that love was the most likely central element for all four groups, and that the change from not being in a relationship until having a long steady partner corresponds to a transition between two stable organization structures through a fragmentation of meanings associated with intermediate relationship situations. It is concluded from results that participants in different relationship configurations relate to a single representation on couple relationships, but that its expression is influenced by modulations associated with specific relationship contexts.